Public Private Partnership ( Studi Kasus Penataan Shelter PKL Simpang Lima Kota Semarang ) - Putra C Mahardika; Muh Adnan; Sulistyowati . (Journal of Politic and Government Studies, 2013)
The issue of Street Vendors often appear in town big city, not to mention the city of Semarang. In this case the street vendors who are in Simpang Lima area, where the area has been constructed walkways used to organize street vendors in the area to make it more organized and do not disrupt public order. Semarang City Government through the Office Market has the initiative to organize a food court area to invite the private sector to cooperate. The purpose of this study is to investigate the implementation of the cooperation between the government and the private sector in an effort to make the existing arrangement of street vendors in the city of Semarang Simpang Lima area. And identify issues and impacts arising from the implementation of such cooperation. To address concerns and objectives of this study, the authors used a qualitative descriptive approach. The results showed that co-operation does not go smoothly, traders feel aggrieved because private sector demand to sell drinks at the shelter. Government can not be a mediator in the resolution of the issue between the traders and the private sectors. About the sustainability of cooperation for the future, the Government, the private sector and the traders should periodically evaluate the operation of the partnership to identify the weaknesses and shortcomings in the operation of the shelter Simpang Lima cooperation arrangement that could be beneficial to both parties and the general public. Keywords: street vendors, Cooperation, Government and Private